FUNGSI KONSUMSI RUMAH TANGGA DI INDONESIA (Pendekatan Model Koreksi Kesalahan) - Sangadji, Maryam (IQTISHODUNA, 2008)
Keynesian theory about consumption states that household consumption (C) related positively with present income: the greater income the more consumption. Beside that, interest rate influence negatively toward household consumption, because if the interest rate is low then the loan cost  also low, so the factor encourage household to increase it consumption. The results showed that income level related positively with  household consumption level. While the interest rate related negatively  with consumption level. It means that the greater income encourage the household to increase its consumption. But the increase is not as high as the income level. Then the higher interest rate will cause the household increase its saving, so decrease the consumption. The test by using error correction model (ECM) showed that balance  variable of ECT is significant, where for that the household consumption adapted with the income level change and the interest rate at the same period.